PEMANFAATAN PLATFORM PEMBELAJARAN ONLINE INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V DALAM KURIKULUM MERDEKA - Ni Wayan Meniasih; Achmad Ramadhan; Oktarafikayanti (EDU RESEARCH, 2024)
This study aims to analyze the effect of using interactive online learning platforms to improve the learning motivation of fifth-grade students at SDN 22 Palu. This research employs a Classroom Action Research (CAR) method with two cycles, involving 27 students. The platforms used are Wordwall, Educaply, and Spinter, which were applied to enhance student engagement, interest, enthusiasm, and satisfaction with the learning process. The results show a significant increase in student engagement, from 55% in the first cycle to 85% in the second cycle. Additionally, students' interest and curiosity also increased, along with higher enthusiasm and satisfaction with this technology-based learning. In conclusion, the use of interactive online learning media significantly improves students' learning motivation. This study suggests that teachers should optimize the use of technology in education to improve student learning outcomes.